The Relationship between Self-Care Needs and Hypertension Control as a Means of Preventing Medical Emergencies in Patients with Chronic Kidney Disease - Aneu Rahmawati; Shinta Arini Ayu; Obar (Jurnal Kesehatan Komunitas Indonesia, 2026)
Background: Chronic kidney disease is often accompanied by hypertension and carries a risk of medical emergencies. Blood pressure control can be achieved through self-care practices, particularly dietary salt reduction. Objective: This study aims to determine the relationship between self-care requisites and blood pressure control in patients with chronic kidney disease. Methods: This cross-sectional study involved 109 respondents selected through accidental sampling. Data were collected using the Dietary Salt Reduction Self-Care Behavior (DSR-SCB) questionnaire and blood pressure measurements, then analyzed using the Chi-square test. Results: Most respondents had adequate self-care (45.0%), while 52.3% had uncontrolled blood pressure. The Chi-square test showed a significant association between self-care level and blood pressure control (p < 0.001), with better self-care correlating with improved blood pressure control. Conclusion: There is a significant association between self-care practices and blood pressure control among patients with chronic kidney disease. Enhanced patient education on self-care, particularly salt restriction, is essential to prevent complications.